INTEGRASI KEPATUHAN HUKUM DAN MITIGASI RISIKO BAGI KORPORASI: PERAN AUDITOR HUKUM DALAM MEMBERIKAN PERLINDUNGAN HUKUM SEHUBUNGAN DENGAN PHK PADA PERUSAHAAN PAILIT - Mona Wulandari; Hendra Apriyanto (LPPM STIH Awang Long, 2025)
The role of legal auditors in providing legal protection in connection with the termination of employment (PHK) of workers in bankrupt companies focuses on ensuring compliance with labor laws and regulations, identifying workers' normative rights, and ensuring that these rights are prioritized in the bankruptcy process. The type of research used in this study is normative juridical. The inconsistency of provisions regarding termination notification between the Bankruptcy Law and the Manpower Law causes uncertainty for workers in preparing themselves for the impact of termination of employment, and makes it difficult for curators to carry out their duties effectively. The results of interviews revealed that the unclear notification rules and priority of payment of workers' rights often give rise to practical obstacles and disputes in the bankruptcy process. Practices in countries such as Germany, France, and Japan show that flexible but sufficient notice periods, court supervision, and social security funds for workers laid off due to bankruptcy are important steps to improve worker protection. Companies that are run in accordance with applicable regulations will increase their value. A company's image in the eyes of the public and potential investors. The primary purpose of a legal audit is risk mitigation. Audit results can be used by business actors or investors before making investments or conducting business. Business actors can mitigate risks in investments. In other words, business actors can request legal audit results when making investments or conducting business. This way, business actors can determine whether the party they intend to collaborate with has implemented legal compliance or is in fact non-compliant.